Pengembangan Matrik Lepas Lambat Berbasis EC – PVP K30 Menggunakan Teknik Dispersi Solida Dengan Model Obat Natrium Diklofenak - Arina Swastika Maulita, Yulistia Budianti Soemarie (University of Muhammadiyah Malang, 2012)
This research is a modification of controlled release which beneficially to optimize the medicine reaction and to minimize the fluctuation of blood level in a certain period of the release. The aim of research is to develop the matrixÂ system in ethylcellulose basic PVP K30 which applies dispersion solid method using sodium diclofenac as sample. Resulted four formulas consist of PVP K30 percentages as follow 0%, 5%, 10% and 20%. The different percentages of PVP K30 is aimed to know the formula which produces the releasing result of ND more optimal. This research produces in each formula significant differences (p<0,05). The formula whole percentages of PVP K30 10% has completed the requirements of control release better than the other one, shown the better resistance characteristics and release profile.